Oncology drugs for orphan indications: how are HTA processes evolving for this specific drug category? - Adkins EM; Nicholson L; Floyd D; Ratcliffe M; Chevrou-Severac H (Dove Medical Press, 2017)
Elizabeth M Adkins,1 Lindsay Nicholson,1 David Floyd,1 Mark Ratcliffe,1 Helene Chevrou-Severac2 1PHMR, London, UK; 2Takeda Pharmaceuticals AG, Zurich, Switzerland Abstract: Orphan drugs (ODs) are intended for the diagnosis, prevention, or treatment of rare diseases. Many cancer subtypes, including all childhood cancers, are defined as rare diseases, and over one-third of ODs are now intended to treat oncology indications. However, market access for oncology ODs is becoming increasingly challenging; ODs are prone to significant uncertainty around their cost-effectiveness, while payers must balance the need for these vital innovations with growing sensitivity to rising costs. The objective of this review was to evaluate different mechanisms that have been introduced to facilitate patient access to oncology ODs in five different countries (Australia, Canada, England, France, and Sweden), using eight oncology ODs and non-orphan oncology drugs as examples of their application. A targeted literature review of health technology assessment (HTA) agency websites was undertaken to identify country-specific guidance and HTA documentation for recently evaluated oncology ODs and non-orphan oncology drugs. None of these countries were found to have explicit HTA criteria for the assessment of ODs, and therefore, oncology ODs are assessed through the usual HTA process. However, distinct and additional processes are adopted to facilitate access to oncology ODs. Review of eight case-study drugs showed that these additional assessment processes were rarely used, and decisions were largely driven by proving cost-effectiveness using standard incremental cost-effectiveness ratio (ICER) thresholds. The predominant implication arising from this study is that application of standard HTA criteria to oncology ODs in many countries fails to take into account any uncertainties around their clinical- and cost-effectiveness, resulting in disparities in HTA reimbursement decisions based on differences in addressing or accepting uncertainty. In order to address this issue, HTA agencies should adopt a more flexible approach to cost-effectiveness, as typified by the Tandvårds-och Läkemedelsförmånsverket in Sweden, which takes into account the small patient numbers involved, limited budget impact, and high unmet medical needs. Keywords: orphan drugs, health technology assessment, oncology, rare cancers